Hydrophobic and lipophilic cellulose nanocrystal aerogel prepared by methyltrichlorosilane via vapor‐phase reaction. Issue 43 (25th August 2022) - Wang, Xingjuan; Xie, Zhongyuan; Chen, Zhangyun; Jiang, Hua
Abstract: Hydrophobic and lipophilic cellulose nanocrystal (CNC) aerogel was prepared by vapor‐phase reaction using methyltrichlorosilane (MTS). The water contact angle of the MTS‐CNC aerogel was up to 148.5°. The residual Cl element in MTS was negatable in the modified CNC aerogel. The MTS‐CNC aerogel only adsorbed the paraffin, but no water was adsorbed. The pseudo‐first‐order kinetic model could well describe the adsorption of the liquid paraffin oil on the CNC aerogel and the maximum adsorption capacity was about 60 g g −1 at 40°C. Multiple steps controlled the whole adsorption of oil on the MTS‐CNC aerogel, but 90% of the maximum adsorption capacity of paraffin was taken up in the first 1 min. The vacuum desorption could effectively remove the adsorbed oil at 80°C, and the good performance of the MTS‐CNC aerogel in adsorption and desorption was retained during 5 cycles. Therefore, the MTS‐CNC aerogel could be a potential candidate for removing oil from the oil‐spilled water system. Abstract : Vapour‐phase reaction of CNC aerogel with MTS followed by its adsorption of paraffin and the desorption